Phosphorus-reducing technologies in swine production - Michael A Boland; K A Foster; P V Preckel (Kansas Agricultural Experiment Station Research Reports, 1998)
Soil phosphorus levels have increased as swine production has become concentrated. Phosphorus-based manure management regulations for land application have been proposed by policy makers. The objective of this research was to determine benefits/costs of adopting phytase for reducing phosphorus. Results were derived using different manure storage and application systems. Although phytase was a least-cost ingredient, it became profitable when producers were constrained by land. Land requirements were 2 to 5 times greater under a phosphorus application regulation than a nitrogen application regulation.; Swine Day, Manhattan, KS, November 19, 1998
Keywords: Swine day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 819; Swine; Management; Manure; Nitrogen; Phosphorus; Phytase